Perception of PAI IAIN Ternate Students on the Concept of Religious Tolerance and Moderation: Between Curriculum Narrative and Campus Social Reality - Minabari, Khalid Hasan; Adam, Adiyana; Limatahu, Kartini; Sebe, Kamarun M.; Silawane, Nurjannah (Electronic Journal of Education, Social Economics and Technology, 2025)
This study investigates the perceptions of Islamic Religious Education (PAI) students at IAIN Ternate regarding religious tolerance and moderation, highlighting the gap between curriculum narratives and social realities on campus. Although religious moderation has been integrated into the curriculum as part of national Islamic education policy, many students still exhibit exclusive attitudes and discomfort in interfaith interactions. A survey revealed that 45% of students feel uneasy interacting with peers from different religious backgrounds, and 30% tend to engage in rigid, non-dialogical religious discussions. These findings indicate a challenge in translating theoretical knowledge into practical behavior. The study uses a qualitative approach to explore how moderation values are internalized in students’ academic and social environments. It found that while students understand the concept intellectually, its application remains limited due to socio-cultural factors. The results suggest the need for more contextual and interactive learning strategies that can bridge this gap such as value-based discussions, pluralism-based student programs, and inclusive role models. This research provides valuable insights for curriculum developers and educators aiming to cultivate religious moderation as a lived value, not merely a theoretical concept, particularly in multicultural Islamic higher education settings like IAIN Ternate.